Conceptual analysis of the relationship between culture and education - Monika Veronika; Firman Firman; Riska Ahmad (Indonesian Counselor Association (IKI), 2021)
Culture is a complete collection of customs, values, arts, knowledge, morality, rules, and other practices that are owned as human beings and as members of society by individuals. By a long process, namely through socialization and education, this can be realized. Education is the process by which each person is civilized, which is created by a great desire to learn, which is created to become a full member of a community, living and upholding the values expressed in a specific culture by a group of people. The most productive way is to conserve, preserve and disseminate culture by education. They both have a very close bond since they complement each other and encourage each other. A type of library research is the type of research used in this manuscript. The aim of the debate on the relationship between culture and education is to make people understand that culture and education are two sustainable things.